WISATA SEPEDA DALAM MEWUJUDKAN PARIWISATA BERKELANJUTAN DI SANUR - Wirawan, Komang (JURNAL MASTER PARIWISATA; Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p01)
Cycling tourism is a recreational activity in a vacation far from home or everyday life in which riding a bicycle constitutes the basic and significant part. Sanur, well-known by tourists as a holiday spot where bicycles are easy to find and commonly used as a transportation mode, has some potentials conducive to the development of cycling tourism. They have also been reinforced with the stakeholders’ planning and activities in the hope that this type tourism activity can keep growing for the local people and tourists to eventually bring about sustainable tourism. The planning covers public policies, physical development for cyclists, the establishment of cycling lanes, the making of maps, and promotions that involve all stakeholders. This research was carried out by identifying potential based on the tourism components of 4-A of Attractions, Accessibility, Amenities,and Ancillary, available at Sanur are related to the development of cycling tourism. The research concludes that cycling tour has been developed in Sanur and has the potential to support the sustainability of the destination.
Keywords: cycling tourism, tourism components, sustainable tourism, Sanur.